Completion of Nonreducible Le Fort Fractures by Le Fort I Osteotomy. Issue 1 (January 2015) - Scolozzi, Paolo; Imholz, Benoît
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to prospectively evaluate the use of a simultaneous Le Fort I osteotomy for completion of nonreducible Le Fort fractures. We analyzed the clinical and radiological data of 44 patients with Le Fort fractures, 9 of whom presented with a nonreducible type. Seven patients with an incomplete Le Fort I fracture had a contralateral Le Fort I osteotomy, and 2 patients with an incomplete Le Fort III fracture had a true bilateral Le Fort I-type osteotomy. We recorded age and sex, mechanism of injury, level of Le Fort fracture, concomitant mandibular fractures, concomitant maxillomandibular fixation (MMF) and its duration, surgical approach, status of healing, and complications. Follow-ups were at 1 week and 1, 3, 6, and 12 months. All patients recovered their normal pretrauma occlusion without the need for postoperative elastic guidance, except for 1 patient who required light class III traction elastics for 3 weeks to achieve the correct occlusion. None of the patients presented with intraoperative or postoperative complications. The present study has demonstrated that completion of nonreducible Le Fort fractures by Le Fort I osteotomy results in a high rate of success.